PENGARUH STRUKTUR MODAL DAN INVESTMENT OPPORTUNITY SET TERHADAP KUALITAS LABA DENGAN TATA KELOLA SEBAGAI PEMODERASI - Afriani, Yossy; Trisnawati, Estralita (Fakultas Ekonomi Universitas Tarumanagara, 2025)
The purpose of this study was to determine the effect of capital structure and investment opportunity set (IOS) on earnings quality, with corporate governance as a moderating factor. Earnings quality is crucial for decision-making because it can assess a company's success or failure in achieving its operational goals. Earnings quality can indicate the quality of earnings by indicating the company's financial condition and measuring financial performance. When a company achieves optimal results and provides accurate information to aid decision-making, earnings can be considered high-quality. The quantitative secondary data method used purposive sampling with 84 manufacturing companies listed on the Indonesia Stock Exchange (IDX) for five years, from 2018 to 2022, using eViews version 12 and SPSS version 27. The results showed that capital structure had no effect on earnings quality, investment opportunity set (IOS) did not affect earnings quality, corporate governance did not moderate the relationship between capital structure and earnings quality, and corporate governance did not moderate the relationship between investment opportunity set (IOS) and earnings quality. The purpose of this study was to determine the effect of capital structure and investment opportunity set (IOS) on earnings quality, with corporate governance as a moderating factor. Earnings quality is crucial for decision-making because it can assess a company's success or failure in achieving its operational goals. Earnings quality can indicate the quality of earnings by indicating the company's financial condition and measuring financial performance. When a company achieves optimal results and provides accurate information to aid decision-making, earnings can be considered high-quality. The quantitative secondary data method used purposive sampling with 84 manufacturing companies listed on the Indonesia Stock Exchange (IDX) for five years, from 2018 to 2022, using eViews version 12 and SPSS version 27. The results showed that capital structure had no effect on earnings quality, investment opportunity set (IOS) did not affect earnings quality, corporate governance did not moderate the relationship between capital structure and earnings quality, and corporate governance did not moderate the relationship between investment opportunity set (IOS) and earnings quality.